A RESEARCH ON INVESTIGATING CUSTOMER CONTENTMENT AND ATTITUDES TOWARDS INTERNET BANKING FACILITIES IN SALEM DISTRICT - Geetha, S; Manivannan, M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In our fast-paced lives, we are constantly being tested on our skills and endurance. Everyone must strive to find ways to save time. One of the innovative advancements that allows customers to carry out their financial transactions from a physical or online bank, credit union, or other financial institution on a secure platform is online banking. Online banking, also known as electronic banking, is the digital delivery of traditional banking services and products to customers directly through electronic, interactive communication channels. It offers customers numerous benefits and conveniences over traditional banking. Online banking is a fast and convenient way to access your bank account using your mobile phone. Online banking uses the internet to facilitate financial transactions. When it comes to everyday tasks, bank transfers are a thing of the past thanks to online banking services. One of the most popular services offered by banks is online banking, making it a highly reliable platform. Banks often use encryption systems to safeguard the security of all customer data and prevent data breaches. Ultimately, it protects against online fraud and account manipulation. The speed of internet access, the new online banking features, and the frequency of online banking usage all impact how quickly online banking develops in each country. When the operations of banks and financial institutions are combined with information technology, online banking is created in the banking sector. Therefore, this study aims to provide an analytical view of customer satisfaction and preference for online banking services in Salem district.